Be good to your patient: how the therapeutic relationship in the treatment of patients admitted to assertive outreach affects rehospitalization. - Fakhoury, W; White, I; Priebe, S (2007)
We investigated whether the quality of the therapeutic relationship (TR) between patient and clinician predicts rehospitalization in patients in assertive outreach treatment. Analyses were conducted on 332 "established" (equal to in care for > or =3 months) and 150 "new" (equal to in care for <3 months) patients with severe mental illness sampled from 24 assertive outreach teams in London, England. TR was assessed at baseline using the clinician version of the Helping Alliance Scale. Rehospitalization was assessed over a 9-month follow-up period. Controlling for other predictors, a more positive TR was found to predict fewer hospitalizations in new patients but not in established ones.